USING RAPD AND ENHANCED-RAPD MARKERS TO DISTINGUISH BETWEEN MANGIFERA APLANATA KOSTERM. AND ITS RELATED SPECIES - Fitmawati Fitmawati; Alex Hartana (PTTI, 2010)
Fitmawati & Alex Hartana. 2010. Using RAPD and Enhanced-RAPD Markers to Distinguish Between Mangifera aplanata Kosterm. and Its Related Species. Floribunda 4(1): 1–4.— RAPD and E-RAPD analysis of M. aplanata were observed in reactions with 27 primers. Four out of these 27 primers produced 10 specific bands patterns. The result can distinguish M. aplanata from its closely related species. Fourtysix polymorphic fragments were amplified, which represents 89.1 percent of the total band number. The length of these fragment ranged from about 200 to 1500 bp.